Polymorphism of 9p21.3 locus is associated with 5-year survival in high-risk patients with myocardial infarction. - Anna Szpakowicz; Witold Pepinski; Ewa Waszkiewicz; Dominika Maciorkowska; Małgorzata Skawronska; Anna Niemcunowicz-Janica; Robert Milewski; Sławomir Dobrzycki; Włodzimierz Jerzy Musial; Karol Adam Kaminski (PLoS ONE, 2013)
OBJECTIVE: The rs1333049, rs10757278 and rs4977574 are single nucleotide polymorphisms (SNPs) of chromosome 9p21 locus that are associated with prevalence of acute coronary syndromes (ACS). The rs1333049 SNP was also associated with cardiac outcome 6 months post ACS. No data concerning their association with long term prognosis after myocardial infarction is available. The aim of our study was to investigate the association of the 9p21.3 locus with 5-year overall mortality in patients with ST-elevation myocardial infarction (STEMI) treated invasively. MATERIALS AND METHODS: We performed a retrospective analysis of data collected prospectively in a registry of consecutive patients with STEMI treated with primary PCI. Genotyping was performed with a TaqMan method. The analyzed end-point was total 5-year mortality. RESULTS: The study group comprised 589 patients: 25.3% of females (n = 149), mean age 62.4±11.9 years, total 5-year mortality 16.6% (n = 98). When all the study group was analyzed, no significant differences in mortality were found between the genotypes. However, in high-risk patients (Grace risk score ≥155 points, n = 238), low-risk homozygotes had significantly better 5-year survival compared to other genotypes. The hazard ratio associated with high-risk genotype (high-risk homozygote or heterozygote) was: HR = 2.9 (95%CI 1.4-6.1) for the rs4977574 polymorphism, HR = 2.6 (1.25-5.3) for the rs1333049 one and HR = 2.35 (1.2-4.6) for the rs10757278 one (Cox proportional hazards model). CONCLUSIONS: The 9p21.3 locus is associated with 5-year mortality in high-risk patients with STEMI. This finding, due to very high effect size, could potentially be applied into clinical practice, if appropriate methods are elaborated.